INTERPROFESIONAL COLLABORATION MELALUI PROMOSI KESEHATAN SEBAGAI UPAYA PENANGGULANGAN HIPERTENSI PADA LANSIA DI WILAYAH DESA TROSEMI, KECAMATAN GATAK, KABUPATEN SUKOHARJO - Dian Maulida Ahsan; Ananta Rinasari Kusumaningrum; Ameliya Dewi Anjani; Dyah Cahyanngsih; Ajeng Puja Ningtyas; Siti Rahmi Mafdhukah; Oktaviana Citra Permatasari; Franciska Yulia Hapsari; Nur Mahes Adi Putra; Asem Abdullah Ahmed Abdo; Sugiharto Sugiharto; Izzatul Arifah (Universitas Muhammadiyah Surakarta, 2026)
Hypertension is one of the non-communicable diseases (NCDs) that is the main cause of morbidity and mortality in Indonesia, with a prevalence that continues to increase every year. The low level of public knowledge, especially the elderly, regarding risk factors, symptoms, and prevention of hypertension is a challenge in controlling this disease. Community service activities carried out by KKN Group 40 Students of Muhammadiyah University of Surakarta in Trosemi Village, Gatak District, Sukoharjo Regency, aim to increase the knowledge and awareness of the elderly about hypertension. The methods used include screening, pre-test, education, discussion, and post-test. The target of the activity is the elderly at the SidoMulyo Posyandu which is carried out through blood pressure checks, educational lectures using leaflets and posters, and hypertension exercises. The results of the activity showed an increase in participant knowledge after the activity, as evidenced by a significant difference between the pre-test and post-test values (p<0.05). This community service activity has achieved its goal of increasing the knowledge of the elderly in Trosemi Village who participated in the Lansia Posyandu activities at the Sido Mulyo Posyandu. This activity has proven effective in increasing the elderly's understanding of hypertension and is expected to contribute to behavioral changes towards a healthier lifestyle. It is recommended that similar programs be implemented sustainably and become part of routine activities at the integrated health post.